(De)politicization of COVID-19 Pandemic in the Implementation of 2020 Simultaneous Regional Elections - Yuseptia Angretnowati; Palupi Anggraheni (Jurnal Sosial Humaniora, 2021)
Coronavirus disease (COVID-19) takes effect on state management inIndonesia. Good crisis management is necessary to mitigate COVID-19. Thisresearch uses Beland ‘s conceptual framework on politics of insecurity and itsimplementation on the state's management crisis process, especially on howthe state protects its citizens towards non-traditional threads whileperforming political accountability. The 2020 Simultaneous RegionalElection (Pilkada) during pandemic is positioned as a case study, especiallyon how policy conflicts and calculation of benefits-risks occur. It has a pivotalrole in establishing perception of collective thread. In the case of 2020Simultaneous Regional Election, conflict in policy creates social anxiety andpolitical tension caused by a health crisis. This research finds that thegovernment (de) politicized the 2020 Simultaneous Regional Elections byusing a repertoire of types of strategies, i.e: avoiding blame and claimingcredit, which were carefully compiled and implemented in a specific frame.